Penerapan Pencatatan Akuntansi Berdasarkan PSAK 45 pada Masjid Al-Islah Cisaat Sukabumi - Zaky, Muhammad; Suaebah, Ebah (PT. Alahyan Publisher Sukabumi, 2024)
This study utilizes a qualitative research approach with a descriptive strategy. The aim of the study is to examine the implementation of accounting records in compliance with PSAK 45 at Al-Islah Mosque, Cisaat District, Sukabumi Regency. This study employs primary and secondary data gathered from observations, interviews, and the literature and material pertaining to the Al-Islah Cisaat Mosque in Sukabumi. The study's findings demonstrate that the financial report of the Al-Islah Mosque Cisaat Sukabumi, as evaluated by the researcher, exhibits a lack of knowledge and proficiency among the accounting personnel, leading to the financial statements not conforming to PSAK No. 45. The mosque's accounting staff must apply PSAK No. 45 to compile their financial statements. In accordance with PSAK No. 45, the financial status statement of Al-Islah Mosque reveals total assets of Rp. 23,500,000, which aligns with the total obligations and fund balance. Net asset activity report and cash flow statement amounting to IDR 11,500,000. The PSAK No. 45 report is expected to provide a basis for improved decision-making in the financial management of the Al-Islah Cisaat Sukabumi mosque.